Future perspective for potential Helicobacter pylori eradication therapies. (24th May 2018) - Debraekeleer, Ayla; Remaut, Han
Helicobacter pylori infection of the human stomach causes chronic inflammation and forms a major risk factor for the development of peptic ulcer disease and gastric cancer. Current standard eradication therapies use an acid-suppressing drug and two antibiotics, now frequently supplemented with bismuth. Declining eradication efficiencies, off-target effects of lengthy broad-spectrum antibiotic treatments and the desire of a more systematic eradication in asymptomatic H. pylori carriers to suppress gastric cancer incidence spur a search for an effective vaccine and alternative therapeutic options. Here, we review the current progress in the field, with an emphasis on narrow-spectrum or nonantibiotic therapeutics.